Pleuropulmonary blastoma in a 3-year-old child with persistent fever: a case report - Yue, Ruiqi; Ma, Guixia; Mao, Li; Ni, Qian (Frontiers in Pediatrics, 2025)
Pleuropulmonary blastoma (PPB) is a rare and highly aggressive malignant mesenchymal tumor, representing the most common malignant lung tumor in children. It is often misdiagnosed or underdiagnosed due to its clinical presentation, which mimics acute respiratory infections. Additionally, imaging manifestations are frequently indistinguishable from congenital respiratory malformations or severe lung infections. The tumor has high rates of recurrence and metastasis and has a poor prognosis. Currently, the internationally recommended treatment for PPB is a combination of surgery, chemotherapy, and radiotherapy. This article discusses the diagnosis and treatment of a 3-year-old girl with PPB combined with severe pneumonia.